2011
DOI: 10.1016/b978-0-12-387036-0.00005-0
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish Lipid Metabolism: From Mediating Early Patterning to the Metabolism of Dietary Fat and Cholesterol

Abstract: Lipids serve essential functions in cells as signaling molecules, membrane components, and sources of energy. Defects in lipid metabolism are implicated in a number of pandemic human diseases, including diabetes, obesity, and hypercholesterolemia. approaches for disease prevention and treatment. Numerous studies have shown that the zebrafish is an excellent model for vertebrate lipid metabolism. In this chapter, we review studies that employ zebrafish to better understand lipid signaling and metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
123
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(127 citation statements)
references
References 109 publications
(122 reference statements)
2
123
2
Order By: Relevance
“…I) suggested the possibility of assessing other phenotypes beyond 5 dpf, when larvae begin to rely on exogenous sources of nutrients, including lipids, through feeding ( 20,50,51 ). Previous reports have indicated that treatment of 5 dpf larvae with a HCD resulted in elevated total cholesterol after 10 days of feeding, including evidence of increased LDL-c ( 35 ).…”
Section: Increased Ldl-c In Ldlr Morphantsmentioning
confidence: 99%
See 3 more Smart Citations
“…I) suggested the possibility of assessing other phenotypes beyond 5 dpf, when larvae begin to rely on exogenous sources of nutrients, including lipids, through feeding ( 20,50,51 ). Previous reports have indicated that treatment of 5 dpf larvae with a HCD resulted in elevated total cholesterol after 10 days of feeding, including evidence of increased LDL-c ( 35 ).…”
Section: Increased Ldl-c In Ldlr Morphantsmentioning
confidence: 99%
“…This would potentially correlate with increased transcription of ldlr , though additional transcripts would likely continue to be targeted by the MO in our model. The yolk plays a critical role in lipid metabolism in early development ( 8,50 ) and it is diffi cult to differentiate between changes that might affect the yolk, thereby affecting lipid traits in the embryo, compared with changes specifi c to experimental manipulation. It is important to note that, although we detected expression of ldlr at earlier stages when the yolk was still present, we did not assay cholesterol levels or induce dietary manipulations until after the stage at which the yolk was depleted and larvae began to feed.…”
Section: Increased Liver Lipid Accumulation and Hepatomegaly In Ldlr mentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, tank densities were different between the two studies, with the current study having three times the density of the previous work (e.g., current: *5.5 fish/L vs. *1.6 fish/L). 24 Although the zebrafish model has garnered much recent attention for its potential use in lipid and obesity research, [41][42][43][44][45][46][47] few studies have reported overall body composition outcomes. In the present work, the dietary protein source significantly impacted lean and fat mass outcomes.…”
Section: Smith Et Almentioning
confidence: 99%